The representation of white working class women in the construction of a reactionary Populist movement: 'Purified' Afrikaner Nationalist agitation for legislation against 'mixed' marriages 1934-1939 - Hyslop, Jonathan (My University, 1993)
In May 1938, the largely white South African electorate went to the polls. But the question which had preoccupied participants in the preceding weeks of the election was not, as one might imagine, the segregationist policies of General Hertzog's government or the economy's gradual emergence from the depths of the Great Depression. Rather, debate and agitation focused on an image of white womanhood. That image was contained in a poster distributed by the ‘Purified’ National Party (Gesuiwerde Nasionale Party) (GNP) of Daniel Francois Malan, and was a pictorial representation of the GNP's contention that Hertzog, through his ‘Fusion’ alliance with pro-British forces of General Jan Smuts to form the United Party (UP), had sold out Afrikaner political interests, in particular by adopting insufficiently aggressive racial policies.
African Studies Seminar series. Paper presented 24 May, 1993
Keywords: Women. Political activity. South Africa; Segregation. Law and legislation. South Africa